Lipid and polyphenol removal on the structural, physico-chemical and technological properties of passion fruit epicarp flour - Xin Ning; Chengrong Wen; Shimin Chen; Lina Chen; Xiaohui Huang; Lei Wang (Food Chemistry: X, 2025)
The effects of defatting and dephenolization treatments on the structural, physico-chemical and technological properties of passion fruit epicarp flour (PFEF) were evaluated in this research. The FT-IR, SEM and XRD results illustrated that defatted and defree phenolics did not change the basic chemical structure of PFEF, while debound phenolics treatment hydrolyzed the ester bonds between dietary fiber and polyphenols and hydrolyzed the amorphous region of dietary fiber, resulting in self-assembly into a larger aggregate with a compact texture. All three kinds of treatment could improve the flowability of passion fruit epicarp flour to some extent. In addition, dephenolization treatment brought about an obvious change in the technological properties of PFEF, and removal of free polyphenols or bound polyphenols contributed to two completely different effects on partial indicators. These properties may be important for their value-added utilization.